The management of turn transition in signed interaction through the lens of overlaps - Girard-Groeber, Simone (Frontiers in Psychology, 2015)
There have been relatively few studies on sign language interaction carried out within the framework of conversation analysis (CA). Therefore, questions remain open about how the basic building blocks of social interaction such as turn, turn construction unit (TCU) and turn transition relevance place (TRP) can be understood and analysed in sign language interaction. Recent studies have shown that signers regularly fine-tune their turn-beginnings to potential completion points of turns (De Vos, Torreira & Levinson, 2015; Groeber, 2014; Groeber & Pochon-Berger, 2014). Moreover, signers deploy practices for overlap resolution as in spoken interaction (McCleary & Leite, 2013). While these studies have highlighted the signers’ orientation to the ‘one-at-a-time’ principle described by Sacks et al., (1974), the present article adds to this line of research by investigating in more detail those sequential environments where overlaps occur. The contribution provides an overview of different types of overlap with a focus of the overlap’s onset with regard to a current signer’s turn. On the basis of a 33-minute video-recording of a multi-party interaction between 4 female signers in Swiss German Sign Language (DSGS), the paper provides evidence for the orderliness of overlapping signing. Furthermore, the contribution demonstrates how participants collaborate in the situated construction of turns as a dynamic and emergent gestalt and how they interactionally achieve turn transition. Thereby the study adds to recent research in spoken and in signed interaction that proposes to rethink turn boundaries and turn transition as flexible and interactionally achieved.